2006
DOI: 10.1101/gad.1471106
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α delays premature senescence through the activation of MIF

Abstract: Premature senescence in vitro has been attributed to oxidative stress leading to a DNA damage response. In the absence of oxidative damage that occurs at atmospheric oxygen levels, proliferation of untransformed cells continues for extended periods of time. We have investigated the role of the hypoxia-inducible factor 1␣ (HIF1␣) transcription factor in preventing senescence in aerobic and hypoxic conditions. Using embryonic fibroblasts from a conditional HIF1␣ knockout mouse, we found that loss of HIF1␣ under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 34 publications
10
146
0
Order By: Relevance
“…Accordingly, the HIF-1alpha (HIF-1α) transcriptional factor has been reported to induce MIF expression by binding to the HRE of the MIF promoter [18,43]. Similarly, we found that activation of the MIF promoter region (−74 to +127 bp) by HIF-1α is dependent on the presence of a functional HRE but not the CRE, and HIF-1α was recruited to this region of the MIF promoter (Supplementary information, Figure S4).…”
Section: Phosphorylation Of S857 Is Required For the Coactivation Of mentioning
confidence: 51%
See 2 more Smart Citations
“…Accordingly, the HIF-1alpha (HIF-1α) transcriptional factor has been reported to induce MIF expression by binding to the HRE of the MIF promoter [18,43]. Similarly, we found that activation of the MIF promoter region (−74 to +127 bp) by HIF-1α is dependent on the presence of a functional HRE but not the CRE, and HIF-1α was recruited to this region of the MIF promoter (Supplementary information, Figure S4).…”
Section: Phosphorylation Of S857 Is Required For the Coactivation Of mentioning
confidence: 51%
“…It was previously shown that expression of MIF is induced by HIF-1α under hypoxia, and that induction of MIF prevents premature senescence by inactivating the p53 tumor suppressor [18]. Although recent genome-wide analysis of SRC-3 chromatin affinity sites in MCF-7 human breast cancer in response to estrogen induction did not identify the MIF gene, high-stringency HIF-binding site(s) near the MIF gene was identified in another recent genome-wide mapping [42,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that cells cultured under hypoxic conditions can acquire the ability to delay the onset of replicative senescence through a mechanism mediated, at least in part, by HIF-1 -dependent up-regulation of hypoxia response element -containing genes such as macrophage migration inhibitory factor (34,35). Although hypoxia may potentially act in a similar fashion to prevent the initiation or maintenance of drug-induced senescence, an alternative mechanism for hypoxia-induced resistance is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies from our laboratory demonstrate that MIF is an important contributor to anchorage independence, cell motility, and invasive potential of A549 lung adenocarcinoma cells (9,10). MIF signals as an extracellular autocrine and paracrine-acting cytokine and is necessary for maximal tumor-associated neovascularization (7,11), evasion from cell senescence (12), and inhibition of the tumor suppressor, p53 (13)(14)(15). Recent studies revealed that the only other known MIF family member, D-dopachrome tautomerase (D-DT), functionally cooperates with, and compensates for, MIF in dictating neoangiogenic potential in human NSCLC cell lines (11).…”
mentioning
confidence: 99%